Series of clinical cases and management of histopathologically diagnosis of squamous cell carcinoma in African pygmy hedgehogs (Atelerix albiventris) - Che' Amat, Azlan; Mazlan, Mazlina; Abba, Yusuf; Abdullah, Faez Firdaus Jesse; Lim, Eric Teik Chung; Haron, Nur Asyikin; Muhamad, Azim Salahuddin; Ahmad Affandi, Syahirah; Abdullah, Abraham Gabriel; Peter, Innocent Damudu; Bitrus, Asinamai Athliamai; Wan Jaafar, Wan Nor Fitri; et al. (Veterinary Association Malaysia, 2020)
Squamous cell carcinoma (SCC) is frequently seen as an invasive cutaneous tumour that can be fatal in animals. In this case series, the clinical management of histopathologically diagnosis of SCC in three different individuals of African pygmy hedgehogs is described. In two of the cases presented, the tumours were presented as an oral mass on the gingiva, which were ulcerative and septic. Lumpectomy was performed in both cases and histopathology revealed encapsulated mass composed of neoplastic cells showing squamous differentiation arranged in islands with presence of keratin pearls, intercellular bridges and frequent mitotic figures which are typical features of squamous cell carcinoma. Following lumpectomy, the two hedgehogs were discharged but were later found to developed ocular lesion and anorexia before they were found dead. In the third case, SCC was diagnosed on the phalanges of the 3rd and 4th digits and surgical resection was successfully performed in this case and post-surgical complications were not recorded. Squamous cell carcinoma is one of the most common malignant tumours in African pygmy hedgehogs. In this case series, three cases of SCC were diagnosed using histopathology which two of the cases had predilections in the oral cavity while the third one only involved the digits.